Advancements in solar updraft towers: a comprehensive review - Natarajan R.; Sambath Y.; Chinnasamy S.; Prakash K.B.; Mohanty A.; Suresh Kumar M.; Arul M. (EDP Sciences, 2025)
The desire for a carbon-free planet has prompted a few experts to advocate for the most abundant energy known to us i.e Solar Energy. There are lots of solar powered energy systems in which the solar chimney power plant has been significant among passive methods in generating carbon free power. There are many attempts taken both experimentally as well as theoretically in developing efficient solar chimneys. This article reviews the major activities carried out in the various topographical regions covering significant research articles. In addition, the survey focuses on experimental research, understanding and recreational works, applications, and analogous work references, all of which are based on a broad range reference. Further, discussion on the research gap in each of the section is included with recommendations for future enhancement of this technology. ? 2024 EDP Sciences. All rights reserved.